Monkeypox Virus: A comprehensive narrative review - Hassan, S; Paudyal, N; Emaan, A; Ibrahim, S (Kathmandu University Medical Journal, 2023)
Monkeypox virus, now known as Mpox virus is a large, enveloped, double stranded deoxyribonucleic acid (DNA) virus belonging to the Orthopox viridae genus of the Poxviridae family. Though, Mpox, have earlier been endemic to only African countries, the 2022 outbreak has shown its rapid spread throughout the world. The May 2022 outbreak have shown primarily human to human transmission in contrast to animal to human transmission that had been seen previously. Recent data also suggest a possibility of a pre symptomatic spread. After an incubation period of 9 days, patients with Mpox can present with a prodrome of symptoms followed by a rash. If untreated, severe complications develop in the high-risk groups especially children and pregnant woman. Such groups of people will benefit from antiviral treatments. The current approach to prevent against it is pre-exposure and post exposure prophylaxis with vaccines. The vaccines that have been approved by Food and Drug Administration to date is ACAM2000 and JYNNEOS. Several diagnostic methods exist, among which polymerase chain reaction has proven to be the most specific and sensitive. In this review, we will discuss its epidemiology, the clinical manifestations, diagnostic modalities, complications, treatment approaches and preventive measures.